Influence of Leadership Style on Performance Contracting Results in Local Authorities, Kenya - Mwangi, Elliubs Kimura; Gakure, Roselyn W; Arasa, Robert; Waititu, Anthony (My University, 2017)
Purpose: The purpose of the study was to investigate the influence of leadership style on performance contracting results in local authorities in Kenya. Methodology: The study used a Correlational research design. The target population comprised of 4I867 employees. This study used stratified random sampling to select a sample of 328 from the175 Local Authorities in Kenya as per the Ministry of Local Government. Questionnaires were used to collect data from local authority employees. Descriptive and inferential statistics was used to conduct analysis. Results: The study found out that Leadership style significantly affect the effectiveness of performance contracting. Unique contribution to theory, practice and policy: The study recommended that local authorities’ management should emphasize and enhance good leadership styles in the organization. The recommendation maybe critical to the successful running of the county governments which takes over the services performed by local authorities.
Keywords: Performance Contracting; Leadership Style; Local Government